Ambon Banana (Musa acuminata) Consumption and Its Effect on Gestational Hypertension Among Pregnant Women - Zuhrotunida Zuhrotunida; Ilma Yani; Murni Lestari (JURNAL INFO KESEHATAN, 2025)
Gestational hypertension is a common pregnancy complication associated with increased risks for maternal and fetal health. Non-pharmacological approaches, including dietary modification, have been explored as potential supportive strategies for blood pressure management. Ambon banana (Musa acuminata) is a potassium rich fruit that may be relevant in this context. This study aimed to examine changes in systolic and diastolic blood pressure following Ambon banana consumption among pregnant women with gestational hypertension attending Puskesmas Jalan Emas, Tangerang Regency. A quantitative pre-experimental study using a one-group pretest-posttest design was conducted among 31 pregnant women aged 23 to 30 years. Participants consumed two Ambon bananas per day, approximately 200 grams, for seven days. Blood pressure was measured before and after the intervention period. Descriptive statistics and paired t tests were used to assess changes in blood pressure. Mean systolic blood pressure decreased from 147.2 ± 5.0 mmHg to 127.0 ± 5.2 mmHg, and mean diastolic blood pressure decreased from 94.2 ± 4.0 mmHg to 83.4 ± 3.1 mmHg, with both changes reaching statistical significance (systolic p = 0.0001; diastolic p = 0.0005). Given the absence of a control group and the small sample size, these findings should be interpreted as preliminary and do not establish causality. The results indicate an observed association between Ambon banana consumption and short term reductions in blood pressure, warranting further investigation through controlled trials with larger samples and longer follow up to determine clinical relevance and generalizability.